2015
DOI: 10.1515/rjr-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Variations of sphenoid pneumatization: a CBCT study

Abstract: The transsphenoidal approach of the skull base has become a usual surgical procedure which targets the sellar, parasellar and suprasellar regions of the middle cranial fossa, as well as Meckel's cave and the clivus 1 . Anatomical studies are essential in increasing the anatomical knowledge and improving surgical performance 2 . Although pituitary surgery is traditionally within the realm of neurosurgeons, otolaryngologists became active partners in the surgical management of hypophysis to decrease rates of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
2
6
0
1
Order By: Relevance
“…Being widely use the Congdon (16) classification, several studies had found that the sellar type is the most prevalent pneumatization, follow by the presellar type and being the conchal type the least common (5,17). Agreeing with this classification, we observed the sellar type as the most frequent type of pneumatization (presented in all cases), followed by the presellar type (case 1 and 3), being less prevalent the conchal type (case 4 on the right side).…”
Section: Discussionmentioning
confidence: 99%
“…Being widely use the Congdon (16) classification, several studies had found that the sellar type is the most prevalent pneumatization, follow by the presellar type and being the conchal type the least common (5,17). Agreeing with this classification, we observed the sellar type as the most frequent type of pneumatization (presented in all cases), followed by the presellar type (case 1 and 3), being less prevalent the conchal type (case 4 on the right side).…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, pneumatization of the sphenoid sinuses extends to adjacent structures such as anterior clinoid processes, pterygoid processes, lesser and great wings of the sphenoid [13]. The greater the pneumatization of sinuses is, the more neurovascular structures burst into sinuses [14].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were placed in the supine position with their chin hyperextended and scan plane angled perpendicular to the hard palate. Axial scans were performed from the maxillary sinus floor to the level of the frontal sinus roof, in a plane parallel with the hard palate [ 10 ]. Images were reviewed on the console with varying window levels and widths.…”
Section: Methodsmentioning
confidence: 99%
“…The paired sinuses generally develop asymmetrically, separated by the inter-sinus bony septum [ 7 , 9 ]. During childhood, maturation of the bone from red to yellow marrow takes place in the anterior part of the sphenoid bone [ 10 ].…”
Section: Introductionmentioning
confidence: 99%